Chronic venous leg ulcer treatment: Future research needs. Issue 1 (17th October 2013) - Lazarus, Gerald; Valle, M. Fran; Malas, Mahmoud; Qazi, Umair; Maruthur, Nisa M.; Doggett, David; Fawole, Oluwakemi A.; Bass, Eric B.; Zenilman, Jonathan
Abstract The prevalence and costs of chronic venous ulcer care in the US are increasing. The Johns Hopkins University Evidence‐Based Practice Center recently completed a systematic review of the comparative effectiveness of advanced wound dressings, antibiotics, and surgical management of chronic venous ulcers. Of 10, 066 citations identified in the literature search, only 66 (0.06%) met our liberal inclusion criteria for providing evidence on the effectiveness of interventions for chronic venous ulcers. Based on review of those studies, members of our team and a panel of informed stakeholders identified important research gaps and methodological deficiencies and prioritized specific future research needs. Based on that review, we provide the results of our assessment of future research needs for chronic venous ulcer care. Advanced wound dressings were considered to have the highest priority for future research, followed by venous surgery and antibiotics. An imperative from our assessment is that future research evaluating interventions for chronic venous ulcers meet quality standards. In a time of increasing cost pressure, the wound care community needs to develop high‐quality evidence to justify the use of present and future therapeutic modalities.